2017
DOI: 10.1007/s10797-017-9453-4
|View full text |Cite
|
Sign up to set email alerts
|

VAT and agriculture: lessons from Europe

Abstract: Little has been written about the treatment of agriculture under the value added tax (VAT). This article attempts to fill the void by surveying and evaluating the situation in the Member States of the European Union (EU) and some other countries. Farmers are often exempted from VAT for administrative and political reasons. But this means that the VAT on their inputs cannot be 'washed out' through the tax deduction/credit mechanism. It then has to be borne by the farmers themselves or becomes an indeterminate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 9 publications
(10 reference statements)
0
10
0
Order By: Relevance
“…Farmers remain apprehensive of VAT due to the commonly held belief that this is a complicated tax. As observed by Kondraszuk and Jaworski [2017] and in some other countries, Cnossen [2018] concluded that farmers are often exempted from VAT on administrative or political grounds. However, this means that farmers are unable to discount the VAT paid on their inputs into agriculture.…”
Section: Research Resultsmentioning
confidence: 91%
“…Farmers remain apprehensive of VAT due to the commonly held belief that this is a complicated tax. As observed by Kondraszuk and Jaworski [2017] and in some other countries, Cnossen [2018] concluded that farmers are often exempted from VAT on administrative or political grounds. However, this means that farmers are unable to discount the VAT paid on their inputs into agriculture.…”
Section: Research Resultsmentioning
confidence: 91%
“…The low factor income of many Member States indicates that exempt farmers should not be burdened with VAT inputs and that the cost of enforcement for taxable farmers should be minimized. [11] Modern fiscal policy in the field of agriculture is not objective due to the use of only stimulating instruments of the tax mechanism. Its implementation over time led to a violation of the structure of agricultural production and the competitive environment, a differentiation of the level of tax burden on producers of various forms of business and specialization of production, and a lack of sources of replenishment of local budgets.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…VAT is an effective tool for the economy for several reasons. Author Cnossen [6] argues that, in general, VAT reduces the marginal cost of public finances and is thus an effective tool for increasing the tax ratio of countries that have included VAT in their tax system. According to author Adhikari [7], the effectiveness of VAT is also based on the assumption that this tax is designed effectively and is well enforceable.…”
Section: Introductionmentioning
confidence: 99%